1976
DOI: 10.1093/infdis/134.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Nocardial Infections in the United States, 1972-1974

Abstract: A survey of members of the Infectious Diseases Society of America indicated that nocardial infections are not rare. Probably between 500 and 1,000 cases are recognized in the United States each year, of which 85% are serious pulmonary or systemic infections. Although nocardial infections are usually opportunistic infections in the compromised host, at least 15% of the infections in this series occurred in patients without a definable predisposing condition. Nocardial infections occurred in a random geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
267
1
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(277 citation statements)
references
References 8 publications
8
267
1
1
Order By: Relevance
“…However, it was not until the retrospective analysis by Presant (434). These and other more recent reviews have suggested that nocardiosis is an increasingly recognized cause of opportunistic infection that may be associated with a variety of underlying disorders, receipt of chemotherapeutic agents, or both (41,43,124,641).…”
Section: Nocardia Speciesmentioning
confidence: 99%
“…However, it was not until the retrospective analysis by Presant (434). These and other more recent reviews have suggested that nocardiosis is an increasingly recognized cause of opportunistic infection that may be associated with a variety of underlying disorders, receipt of chemotherapeutic agents, or both (41,43,124,641).…”
Section: Nocardia Speciesmentioning
confidence: 99%
“…7 However, as many as 15 % of Nocardia cases do not have the above-mentioned standard risk factors. 8 In this patient, alcohol was the presumptive cause of a T cell defect. 3 Nocardia is a soil dweller and readily aerosolizes.…”
mentioning
confidence: 78%
“…Although the view has been expressed that nocardia may colonize the respiratory tract particularly in those with chronic obstructive airways disease (Peabody & Seabury, 1960), this is not a common finding (Raich, Casey & Hall, 1961). By contrast, invasive pulmonary infection is the commonest clinical manifestation of systemic nocardiosis and can be caused by all three pathogenic Nocardia species (Beaman et al 1976). Although it is usually an acute or subacute respiratory disease, on rare occasions lesions may persist for many years (Kirby & McNaught, 1946).…”
Section: Secondary Involvement Of the Skin In Systemic Nocardiosismentioning
confidence: 99%
“…Most appear to arise following bloodstream spread but others may result from direct extension from a pulmonary focus through the chest wall. (Beaman et al 1976) the organism was considered to be an opportunistic pathogen in 53 % of 253 cases reported. Immunosuppressive therapy, organ transplants or neoplasia were the commonest underlying factors.…”
Section: Secondary Involvement Of the Skin In Systemic Nocardiosismentioning
confidence: 99%
See 1 more Smart Citation